2022
DOI: 10.1002/pon.5967
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver's perspective on psychosocial issues of paediatric cancer patients during COVID 19 pandemic lockdown

Abstract: Key points The unprecedented pandemic crisis has caused serious changes in the medical care for cancer patients, thereby mandating research studies to focus and understand the psychosocial issues faced by paediatric cancer patients during the pandemic lockdown in India. Paediatric cancer patients irrespective of diagnosis and treatment status were assessed for psychosocial issues (N = 103) and distress (n = 74). Caregivers were chosen as the primary respondents except for distress score in order to obtain da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…When seeking to identify the impact of the COVID-19 pandemic on the care and attention of pediatric and adolescent patients diagnosed with oncological diseases without concomitant COVID-19 diagnosis, 16 studies were found [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . For a better understanding, these studies will be presented with a legend formed by the letter E, followed by a corresponding study number, as follows: Article Letter E + Number [1…16], for example, E1, E2… E16.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When seeking to identify the impact of the COVID-19 pandemic on the care and attention of pediatric and adolescent patients diagnosed with oncological diseases without concomitant COVID-19 diagnosis, 16 studies were found [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . For a better understanding, these studies will be presented with a legend formed by the letter E, followed by a corresponding study number, as follows: Article Letter E + Number [1…16], for example, E1, E2… E16.…”
Section: Resultsmentioning
confidence: 99%
“…The impact on the daily life of children, adolescents, and their families was related to the sanitary lockdown, the prohibition of visits during hospitalization, and the weakening of the family support system during this period.Studies on this matter have been conducted by Gopalakrishnan et al 10 , Atout et al 11 , Dotto et al 14 , Global Health Research Group on Children's Non-Communicable Diseases Collaborative 19 , Sindhu et al 16 , Davies et al 21 and Van Gorp et al 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Stigma was reported as a major concern, with parents and caregivers reporting that responses such as pity from others would cause the patients to lose self-confidence and it was difficult for them to address these issues with their friends to make play or activities more inclusive or suitable to the child's needs. 33 While fewer patients themselves reported distress, 33 parental perception of distress was greater. 32 Across studies, the need for informational support presented either directly 33 or indirectly (as concern over uncertainty of prognosis) as well as a distinct apprehension regarding relapse and subsequently responding to questions related to mortality by the patient.…”
Section: Patient Needs and Psychosocial Concernsmentioning
confidence: 99%
“…32,33 While these overtly appeared physical, they further extended to psychosocial concerns such as low mood, feeling anxious or helplessness, and overall worry about the patient's well-being among caregivers 32,33 The impact on education and activities of the patients were explored with most parents and caregivers reporting concern regarding the child being unable to complete activities or milestones that their peers would be, falling behind and have difficulty cultivating new social relationships and maintaining existing ones. 32,33 Stigma was reported as a major concern, with parents and caregivers reporting that responses such as pity from others would cause the patients to lose self-confidence and it was difficult for them to address these issues with their friends to make play or activities more inclusive or suitable to the child's needs. 33 While fewer patients themselves reported distress, 33 parental perception of distress was greater.…”
Section: Patient Needs and Psychosocial Concernsmentioning
confidence: 99%